Image registration, contour propagation and dose accumulation of external beam and brachytherapy in gynecological radiotherapy. (February 2020) - Swamidas, Jamema; Kirisits, Christian; De Brabandere, Marisol; Hellebust, Taran Paulsen; Siebert, Frank-André; Tanderup, Kari
Highlights: Rigid registration on applicator good for contour mapping and applicator reconstruction. Current DIR algorithms are not yet robust enough to handle complexities. Wide range of uncertainties when using deformable dose accumulation. Direct addition of doses provides reasonable estimate for target, bladder and rectum. Substantial uncertainties if EBRT dose gradients in the region of the BT boost. Abstract: This review provides an overview of the current status of image registration for image guided gynaecological brachytherapy including combination with external beam radiotherapy. Contour propagation between individual fractions and dose accumulation can be useful for cervix cancer radiotherapy. Contour mapping and applicator reconstruction with rigid registration based on the applicator geometry provide good accuracy. However, deformable image registration is particularly challenging in the pelvic region, due to the large and complex deformations caused by tumor shrinkage, bladder and rectum filling, insertion of a brachytherapy applicator and presence of packing material. This causes substantial limitations and uncertainties when using it in the clinical workflow so that the current generation of deformable image registration algorithms is not yet robust enough to handle complexities involving the dose accumulation of external beam and brachytherapy. The direct addition of doses provides a reasonable estimate of the total absorbed dose. However, in case of significant dose gradients from external beam boosts or midline-shielding adding dose contributions from the different radiotherapy modalities and fractions remains subject to large uncertainties.